Dreaming of a better life: child marriage through adolescent eyes - Crivello, Gina (2020)
Putting an end to the practice of child marriage became an international commitment under Sustainable Development Goal 5 that focuses on empowering girls and women worldwide. Dreaming of a Better Life: Child Marriage Through Adolescent Eyes offers fresh insights and evidence to inform these efforts, based on fi ndings from research and intervention projects funded by Canada’s International Development Research Centre (IDRC) to investigate different aspects of child marriage. Spanning rural and urban settings across Bangladesh, Côte d’Ivoire, India, Mali, Niger, Pakistan, Peru, Senegal, Togo and Zambia, the chapters address themes such as adolescent girls’ agency and roles in marital decision-making, teenage motherhood, sexual and gender-based violence against children, and lessons learned from trying to infl uence policies and implement programmes to reduce child marriage. The short chapters, and mix of photo, visual, interview and traditional reporting formats, are designed to appeal to policymakers in their national contexts, as well as resonate with others committed to supporting and empowering marginalised children and young people everywhere.